2015 15th International Superconductive Electronics Conference (ISEC) 2015
DOI: 10.1109/isec.2015.7383455
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of 1/ƒ Noise in Gradiometers for SQUID-Based Ultra-Low Field Nuclear Magnetic Resonance

Abstract: Superconducting wire may trap magnetic flux after being exposed to strong magnetic fields, for example when used as gradiometer material in a SQUID-based ultra-low field nuclear magnetic resonance system. In this work we investigated noise caused by the dynamics of trapped flux in superconducting gradiometers made from different materials. Niobium (Nb), niobium-titanium (NbTi), and tantalum (Ta) wires were tested. Small wire-wound gradiometers were connected to a SQUID sensor. Nb and NbTi wires showed increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This leads to the conclusion that Pb does not trap flux and therefore renders it a potential alternative. In contrast, Matlashov et al [9] observed significant 1/f -noise after pulsed fields using type-I superconductor Tantalum (Ta) pick-up coils which could be eliminated by thermocycling the Ta coil above it's T c . This can be taken as evidence for rearrangement of trapped flux.…”
Section: Introductionmentioning
confidence: 94%
“…This leads to the conclusion that Pb does not trap flux and therefore renders it a potential alternative. In contrast, Matlashov et al [9] observed significant 1/f -noise after pulsed fields using type-I superconductor Tantalum (Ta) pick-up coils which could be eliminated by thermocycling the Ta coil above it's T c . This can be taken as evidence for rearrangement of trapped flux.…”
Section: Introductionmentioning
confidence: 94%
“…With respect to the noise performance, the application of a large B P has been shown to lead to an excess low-frequency noise due to flux trapping in the superconducting pick-up coil [36]. However, it may be avoided by operation at a sufficiently large Larmor frequency [37], a suitable B P ramp down [38] or rapid thermal cycling of the pick-up coil [39]. Consequently, the noise performance is ultimately limited by Johnson noise of the human body which was recently measured at 55 aT Hz −1/2 [40].…”
Section: Theoretical Sensitivity Limits Of 3d Dcncimentioning
confidence: 99%
“…If during prepolarisation the pick-up-coil wire, usually made of the type-II superconductor niobium (Nb), experiences a field above its lower critical field H c1 , flux will be trapped. During the signal acquisition phase when the prepolarization field is removed, rearrangement of the vortices may cause flux jumps resulting in excess low-frequency noise [21,22]. An example is shown on the right in figure 2.…”
Section: Noise Sources Unique To Ulf Mrimentioning
confidence: 99%
“…There appears to be a large spread in the behavior of different Nb wire samples, indicating an unsolved material issue. A possible alternative might be the use of a type-I superconductor such as lead [24] or thermocycling the gradiometer wire as demonstrated by Matlashov et al [22].…”
Section: Noise Sources Unique To Ulf Mrimentioning
confidence: 99%
See 1 more Smart Citation